Training on Making Physics Teaching Modules Based on the POE2WE Model to Implement an Independent Curriculum for High School Teachers in Tasikmalaya Regency - Nana; Ernita Susanti; Yanti Sofi Makiyah (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Along with the implementation of the independent curriculum, there are still many teachers who do not understand the techniques for preparing and developing teaching modules, especially teaching modules based on learning models for student learning activities. Therefore, this community service aims to provide training in preparing teaching modules based on learning models that are in accordance with the demands of the independent curriculum so as to improve the quality of the learning process. The subjects of this activity were 31 high school physics teachers in Tasikmalaya Regency. Implementation of activities uses lecture, discussion and question and answer methods followed by direct practice. In each implementation, the POE2WE learning model is used. The results of this service show the teacher's ability to create open modules based on the POE2WE model. This can be seen from the open modules that have been produced in the process and after service activities. Based on the questionnaire given at the end of the activity, it appears that the direct benefits of the service activities that have been carried out are in the high category with a percentage of 87.06%.